1 + 0 + 0 1 0 0 + 1 + 0 + 1 1 0 1 + ⋯ + a + b + c a b c + ⋯ + 9 + 9 + 8 9 9 8 + 9 + 9 + 9 9 9 9 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Excellent Question. I also solved it almost like you.
The sum is wrong! It must be 36418.5.
Ok, So there are two types of solution. One is discussed above already by Mahan Farzan.
I'd like to discuss another method that takes a bit of thinking but make our lives much easier.
We can rewrite the above equation as
{ ∑ a = 0 9 ∑ b = 0 9 ∑ c = 0 9 ( a + b + c 1 0 0 a + 1 0 b + c ) − f 3 ( 0 , 0 , 0 ) } − { ∑ b = 0 9 ∑ c = 0 9 ( b + c 1 0 b + c ) − f 2 ( 0 , 0 ) }
Here
f
3
(
0
,
0
,
0
)
is the value when
a
=
0
,
b
=
0
,
c
=
0
. For that we can use the limit to find the value of
a
+
b
+
c
1
0
0
a
+
1
0
b
+
c
=
3
a
1
1
1
a
=
3
7
.
Similarly
f
2
(
0
,
0
)
=
2
b
1
1
b
=
5
.
5
.
Now coming to the main part, The triple summation. It's clearly symmetric in a , b and c . Thus there are 6 other similar permutations. Adding them together,
6 ∑ a = 0 9 ∑ b = 0 9 ∑ c = 0 9 ( a + b + c 1 0 0 a + 1 0 b + c ) = ∑ a = 0 9 ∑ b = 0 9 ∑ c = 0 9 ( a + b + c 2 2 2 a + 2 2 2 b + 2 2 2 c ) = ∑ a = 0 9 ∑ b = 0 9 ∑ c = 0 9 2 2 2 = 2 2 2 0 0 0
Thus, ∑ a = 0 9 ∑ b = 0 9 ∑ c = 0 9 ( a + b + c 1 0 0 a + 1 0 b + c ) = 3 7 0 0 0 .
Similarly, 2 ∑ b = 0 9 ∑ c = 0 9 ( b + c 1 0 b + c ) = ∑ b = 0 9 ∑ c = 0 9 ( b + c 1 1 b + 1 1 c ) = ∑ b = 0 9 ∑ c = 0 9 1 1 = 1 1 0 0
Thus, ∑ b = 0 9 ∑ c = 0 9 ( b + c 1 0 b + c ) = 5 5 0 .
Thus The net sum is, { 3 7 0 0 0 − 3 7 } − { 5 5 0 − 5 . 5 } = 3 6 4 5 0 − 3 1 . 5 = 3 6 4 1 8 . 5 .
Can we figure out a generalized solution for this?
Problem Loading...
Note Loading...
Set Loading...
We divide the three digit numbers into 6 groups, depending on how many zeroes and repeated digits they have.
Case 1. No zeroes, no repeated digits.
a + b + c a b c + a + b + c a c b + a + b + c b c a + a + b + c b a c + a + b + c c a b + a + b + c c b a = a + b + c 2 2 2 ( a + b + c ) = 2 2 2
There are ( 3 9 ) possible ways to choose these numbers, so their sum is ( 3 9 ) × 2 2 2 = 1 8 6 4 8 .
Case 2: No zeroes, only 2 repeated digits
a + a + b a a b + a + a + b a b a + a + a + b b a a = 2 a + b 1 1 1 ( 2 a + b ) = 1 1 1
There are 9 × 8 possible ways to choose these numbers, so their sum if 9 × 8 × 1 1 1 = 7 9 9 2 .
Case 3: No zeroes, all 3 repeated digits.
a + a + a a a a = 3 a 1 1 1 × a = 3 7
Since there are 9 possible ways, their sum is 9 × 3 7 = 3 3 3 .
Case 4: 1 zero, two distinct non-zero digit
a + b + 0 a b 0 + a + b + 0 a 0 b + a + b + 0 b a 0 + a + b + 0 b 0 a = a + b 2 1 1 ( a + b ) = 2 1 1
Since there are ( 2 9 ) ways to choose these numbers, so their sum is ( 2 9 ) × 2 7 7 = 7 5 9 6 .
Case 5: 1 zero, two repeated non-zero digit
a + a + 0 a a 0 + a + a + 0 a 0 a = 2 a 2 1 1 a = 1 0 5 . 5
There are 9 ways to choose these numbers, so their sum is 9 × 1 0 5 . 5 = 9 4 9 . 5 .
Case 6: two zeros, one non-zero digit
a + 0 + 0 a 0 0 = 1 0 0
There are 9 ways to choose these numbers, so their sum is 9 × 1 0 0 = 9 0 0 .
Summing up these 6 cases, we find that the sum is 36418.5